PENGARUH APLIKASI ELECTRIC FERTILIZER TERHADAP KERAGAAN TINGGI TANAMAN JAGUNG VARIETAS BISI-18 - Nadhifah Al Indis (Universitas Islam Kadiri, 2021)
Maize (Zea mays L.) is a monocotyledons plant (the seeds contain only one embryonic leaf) and it is classified as an important food crop that is widely cultivated in Indonesia. There are several varieties of Zea mays L. and bisi-18 is the variety has chosen in this research because it is a superior variety with 90% growth power. Electric fertilizer (EF) is a tool for transmitting an electric current into the soil to stimulate plant growth (stimulus growth). Fertilization of plants is divided into 2 types, they are chemical fertilization and physical fertilization. The chemical fertilization includes the use of synthetic chemical fertilizers and organic fertilizers, while for physical fertilization is through stimulation of ions in the soil by an electric current. The physical fertilization using by EF tool is expected can reduce the consumption of synthetic chemical fertilizers and optimize the use of organic fertilizers. So, it can be an alternative environmental friendly fertilizers. The purpose of this study was, designing an EF set tool with a DC voltage with electrode plates to stimulate the growth of Zea mays L., designing automatic irrigation system with a soil moisture sensor, and analyzing the growth of Zea mays L. with electric current from the EF tool and compared to control (without EF tool). The EF set tool is carried out at various voltage, there are 10V, 12V, 15V, and 20V. The results showed that 12V voltage had the best variable to stimulate the growth of Zea mays L.